A Need Analysis on Character-Based Campus Television to Support the Integrated Laboratory of Learning Technology - Sunaryo Soenarto (Faculty of Engineering, Universitas Negeri Yogyakarta, 2019)
The role of Campus Television (TV) in a university can integrate human resources and audio visual laboratory facilities in each faculty, especially to face today’s digital communication era. The objectives of this study were: (1) to determine the academic community's needs for Campus Television media in Universitas Negeri Yogyakarta (UNY) based on faculties, and the academicians status and (2) to map program types broadcasted by the Campus TV in UNY that were expected by UNY academic community. A survey to the academic community in UNY (consisted of lecturers, employees, and students) was conducted as the research method. Electronic-based questionnaires and smartphones with Google form applications were used as the technique in the data collection. The research subjects were 409 respondents. The data analysis technique was descriptive quantitative. This study concluded that (1) lecturer who agreed and doubted about the existence of Campus TV in UNY were 97.33%, and 2.66% respectively; (2) Employees who agreed was 100%; and (3) Students who agreed, doubted, and disagreed about the existence of Campus TV in UNY were 92.63%, 6.31%, and 1.02% respectively. Campus TV broadcasting programs required by the academic community in UNY included: (1) innovative work programs, (2) campus information, (3) campus activity programs (community service, teaching practice, conference), (4) talk show and (5) skills program. This study provided encouragement to academic community of UNY to support the realization of Campus TV as the integrated laboratory for learning technology.